2011
DOI: 10.1089/jop.2010.0192
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Topical Povidone-Iodine and Different Types of Fluoroquinolones in the Sterilization of Bacterial Flora on the Conjunctiva

Abstract: Ciprofloxacin seems to be more effective in conjunctival sterilization. In consideration with high variety of bacterial flora in pretreatment period in ofloxacin group, ofloxacin seems to be superior to povidone-iodine on the reduction of bacterial flora on the conjunctiva.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
(19 reference statements)
1
18
0
5
Order By: Relevance
“…Inoue et al [31] found that the most effective protocol in bacteria elimination was the antibiotic used for 3 days preoperation with an iodine conjunctival sac wash. Coskun et al [32] compared 5% PVI, ciprofloxacin, and ofloxacin. They determined that the most effective means of eradicating conjunctival flora was the use of ciprofloxacin, the second was ofloxacin, and the last was 5% PVI solution.…”
Section: Povidone-iodine In Preoperative Prophylaxismentioning
confidence: 99%
“…Inoue et al [31] found that the most effective protocol in bacteria elimination was the antibiotic used for 3 days preoperation with an iodine conjunctival sac wash. Coskun et al [32] compared 5% PVI, ciprofloxacin, and ofloxacin. They determined that the most effective means of eradicating conjunctival flora was the use of ciprofloxacin, the second was ofloxacin, and the last was 5% PVI solution.…”
Section: Povidone-iodine In Preoperative Prophylaxismentioning
confidence: 99%
“…Several studies also demonstrated that povidone-iodine and different regimens of antibiotics (moxifloxacine, ofloxacin, ciprofloxacin) are highly effective in minimizing conjunctival flora and reducing contamination rate when used just before injections. 20,21 The use of povidone-iodine may be considered a safe prophylaxia as none of our patients developed endophthalmitis. All of our patients received topical ofloxacin 0.3% for postinjection prophylaxis and this regimen was not changed in culture-positive patients as we did not observed any infectious endophthalmitis during the follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…The detailed screening process is described in Fig 1. Of the remaining reports, there were nine RCTs [13, 3037] and fourteen observational studies [2, 1521, 2429, 38]. A total of 21 studies reported the rate of postoperative endophthalmitis [2, 13, 1521, 24, 2729, 38], and 13 studies reported the microbial isolation rate [25, 26, 3037].…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining reports, there were nine RCTs [13, 3037] and fourteen observational studies [2, 1521, 2429, 38]. A total of 21 studies reported the rate of postoperative endophthalmitis [2, 13, 1521, 24, 2729, 38], and 13 studies reported the microbial isolation rate [25, 26, 3037]. Thirty studies [2, 13, 1521, 24, 2730, 3337, 38] included only eyes that received cataract surgery, but an additional four studies [2526, 3132] included other intraocular surgeries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation